Aluminum in plant: Benefits, toxicity and tolerance mechanisms - Ofoe, Raphael; Thomas, Raymond H.; Asiedu, Samuel K.; Wang-Pruski, Gefu; Fofana, Bourlaye; Abbey, Lord (Frontiers in Plant Science, 2023)
Aluminum (Al) is the third most ubiquitous metal in the earth’s crust. A decrease in soil pH below 5 increases its solubility and availability. However, its impact on plants depends largely on concentration, exposure time, plant species, developmental age, and growing conditions. Although Al can be beneficial to plants by stimulating growth and mitigating biotic and abiotic stresses, it remains unknown how Al mediates these effects since its biological significance in cellular systems is still unidentified. Al is considered a major limiting factor restricting plant growth and productivity in acidic soils. It instigates a series of phytotoxic symptoms in several Al-sensitive crops with inhibition of root growth and restriction of water and nutrient uptake as the obvious symptoms. This review explores advances in Al benefits, toxicity and tolerance mechanisms employed by plants on acidic soils. These insights will provide directions and future prospects for potential crop improvement.